Síntese, modelagem molecular e avaliação da atividade farmacológica de N,N-dimetilcarbamatos de cicloexila 2-fenilaminossubstituídos - Bagatin, Mariane Cristovão (2013)
This work reports the synthesis and theoretical-experimental evaluation of novel series of cis and trans N,N-dimethylcarbamates of 2-phenylaminecyclohexyl as potential cholinesterase inhibitors. Firstly, were performed the synthesis and purification of the compounds with the following substituents: aniline, p-methoxyaniline, p-fluoranilina and pnitroaniline. For each series of isomers were utilized differents methodologies described in the literature. The products were characterized by NMR spectroscopic analysis of 1H, 13C and HSQC, and melting point measurements. To determine the conformational preference of cis and trans carbamtes were performed theoretical calculations using the software package Gaussian09. First were performed calculations of potential energy surface with HF/6-31G level of theory, followed by optimization and frequency calculations with B3LYP/6-311++G(d, p) and NBO calculations were performed (version 5.0) with level of theory B3LYP/6-311++G(d, p). For the trans carbamates were observed two conformations one with both substituents in axial (aa) and other with both substituents in equatorial (ee), and this accounts for over 97% of the equilibrium population. For the cis carbamates, were observed two possible rotamers with the carbamate group in the equatorial and the phenylamino group in axial (ea1 and ea2) and two with the carbamate group in axial and the phenylamino group in equatorial (ae1 and ae2), and they had the lowest energy and are responsible for over 80% of the population at equilibrium. 3JHH values obtained from 1H NMR spectra are in agreement with theoretical calculations. To determine the potential anticholinesterase activity of the compounds obtained in this study, enzymatic assays were performed using the modified Ellman's method. Generally, the test showed the cis-trans isomerism does not influence significantly the activity of these compounds, however, the presence of donating and withdrawing substituents at the para position of the aromatic ring may increase or decrease the activity of the compound, depending on the series analyzed. The cis-N,N-dimethylcarbamate of 2-phenylaminecyclohexyl (8a) showed significant inhibition of the AChE enzyme activity (IC50 of 59,2 mmol/L) and a high inhibition in BuChE enzyme activity (IC50 6,0 mmol/L), and this derivative with greater pharmacological potential to combat Alzheimer's disease. Finally, to examine the selectivity of compounds against the enzyme butyrylcholinesterase were realized docking calculations to determine the possible interactions. The calculation showed that compounds interact more effectively with the active site of enzyme BuChE, where the carbamate group is close to key residues of the catalytic triad.